How strong is the macroeconomic case for downward real wage rigidity? - Steinar Holden; Fredrik Wulfsberg (Federal Reserve Bank of Boston, 2007)
This paper explores the existence of downward real wage rigidity (DRWR) in 19 OECD countries, over the period 1973-1999, using data for hourly nominal earnings at the industry level. Based on a nonparametric statistical method, which allows for country- and year-specific variation in both the median and the dispersion of industry wage changes, we find evidence of some DRWR in OECD countries overall, as well as for specific geographical regions and time periods. There is some evidence that real wage cuts are less prevalent in countries with strict employment protection legislation and high union density. Generally, we find stronger evidence for downward nominal wage rigidity than for downward real wage rigidity.
Keywords: J3; J5; C14; C15; E31; 330; Reallohn; Lohnrigidität; Arbeitnehmerschutz; OECD-Staaten